2013
DOI: 10.1021/jm400050y
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Peptidomimetics: Leads for the Design of Bioavailable Mixed Efficacy μ Opioid Receptor (MOR) Agonist/δ Opioid Receptor (DOR) Antagonist Ligands

Abstract: We have previously described opioid peptidomimetic, 1, employing a tetrahydroquinoline scaffold and modeled on a series of cyclic tetrapeptide opioid agonists. We have recently described modifications to these peptides that confer a mu opioid receptor (MOR) agonist, delta opioid receptor (DOR) antagonist profile, which has been shown to reduce the development of tolerance to the analgesic actions of MOR agonists. Several such bifunctional ligands have been reported, but none has been demonstrated to cross the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
150
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(154 citation statements)
references
References 30 publications
4
150
0
Order By: Relevance
“…Specifically, the 2-methylindanyl analogue was synthesized via an aldol condensation followed by a hydrogenation as previously described 1 to form aniline intermediate 7f . The 1-methylindanyl analogues were synthesized as a racemic mixture using a slight modification of methodology originally developed by Kolanos et al 30 that begins with a condensation reaction between indene and 4-acetamidobenzaldehyde, the product of which was hydrogenated and deprotected to yield an aniline intermediate 7g .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the 2-methylindanyl analogue was synthesized via an aldol condensation followed by a hydrogenation as previously described 1 to form aniline intermediate 7f . The 1-methylindanyl analogues were synthesized as a racemic mixture using a slight modification of methodology originally developed by Kolanos et al 30 that begins with a condensation reaction between indene and 4-acetamidobenzaldehyde, the product of which was hydrogenated and deprotected to yield an aniline intermediate 7g .…”
Section: Resultsmentioning
confidence: 99%
“…15 Co-administration of a MOR agonist with a δ-opioid receptor DOR antagonist 6–8 produces antinociception with reduced risk of tolerance and dependence, implicating the importance of reduced DOR signaling in mitigating these undesired properties. However, multi-drug regimens may produce pharmacokinetic complications and lead to low patient compliance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Systemically active peptidomimetics and nonpeptide small molecules have also been reported with a similar pharmacological profile. 10 An example of a mixed agonist small molecule is SoRI 9409, which showed a preferable side effect profile to morphine. However, SoRI 9409 produced limited antinociception in thermal pain models, thereby limiting its potential therapeutic value.…”
mentioning
confidence: 99%
“…In principle, then, substituent modifications at these positions could lead to compounds that interact with a desirable combination of trueμ~ and δ-opioid receptor affinity. It has been found that compounds that combine both μ-agonist and δ -antagonist behavior can minimize at least some of the undesired side-effects that are frequently observed with the use of opioid analgesics[5-7]. It has also been noted that a δ-agonist can counteract the respiratory depression induced by μ-agonists without interfering with antinociceptive activity [8].…”
Section: Introductionmentioning
confidence: 99%